Challenging the secular state: the Islamization of law in modern Indonesia - Salim, Arskal (University of Hawai'i Press, 2008)
Shari'a and the nation-state -- Islamization and nationalism -- The constitutionalization of Shari'a -- The nationalization of Shari'a --The localization of Shari'a in Aceh